Laboratory study of oil saturation and oil/water substitution effects on a sandstone's modulus dispersion and attenuation. Issue 3 (4th May 2019) - Zhao, Liming; Tang, Genyang; Wang, Shangxu; Zhao, Jianguo; Wang, Xingmou; Liu, Haojie; Wei, Guohua; Sun, Chao; Li, Minlong; Li, Min
Abstract: Using the stress–strain oscillation method, we conducted experiments on a sandstone over a frequency range of 1–100 Hz at a differential pressure of 5 MPa to investigate the effects of oil saturation and oil/water substitution on modulus dispersion and attenuation. We first saturated the sandstone with a low viscosity oil (2#) at different saturation degrees, then replaced the 2# oil with a more viscous oil (68#) and finally injected distilled water in the oil-saturated sample. Young's modulus, Poisson's ratio and extensional attenuation were measured during these saturation processes. The measured moduli of this sandstone, when saturated with the 2# oil at different saturation degrees (0% to 100%) or when fully saturated with the 68# oil, manifest little dispersion over the frequency range of 1–100 Hz, and low attenuation was observed. The measured bulk modulus for the oil-saturated sandstone agrees well with the prediction of Gassmann's fluid-substitution theory, suggesting that wave-induced fluid flow (WIFF) plays an insignificant role in control of the bulk modulus when the sandstone is filled with oil. However, as oil saturation and viscosity increase, the shear modulus keeps increasing, violating the Gassmann's fluid-substitution theory, which may be caused by the viscous coupling mechanism. When water was injected into sandstone fully saturated with the 68# oil, distinct modulus dispersion and attenuation were observed. The characteristics of the modulus dispersion and attenuation are consistent with mesoscopic WIFF theory, indicating that mesoscopic WIFF is the main cause of modulus dispersion and attenuation for this sandstone saturated with oil–water mixture at seismic frequencies.